2002
DOI: 10.1176/appi.ajp.159.12.2099
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12, Folate, and Homocysteine in Depression: The Rotterdam Study

Abstract: The association of vitamin B(12) and folate with depressive disorders may have different underlying mechanisms. Vitamin B(12) may be causally related to depression, whereas the relation with folate is due to physical comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
246
4
13

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(281 citation statements)
references
References 6 publications
18
246
4
13
Order By: Relevance
“…Plasma folate level were inversely associated with depression only in the subgroup of middle-aged women (Bjelland et al 2003). In a large group of elderly people (3884 probands), hyperhomocysteinemia, vitamin B12 deficiency, and, to a lesser extent, folate deficiency were all related to depressive disorders (Tiemeier et al 2002). For folate deficiency and hyperhomocysteinemia, the association with depressive disorders was substantially reduced after adjustment for functional disability and cardiovascular disease, but for vitamin B12 this appeared independent.…”
Section: Vitamins B6 and B12mentioning
confidence: 90%
“…Plasma folate level were inversely associated with depression only in the subgroup of middle-aged women (Bjelland et al 2003). In a large group of elderly people (3884 probands), hyperhomocysteinemia, vitamin B12 deficiency, and, to a lesser extent, folate deficiency were all related to depressive disorders (Tiemeier et al 2002). For folate deficiency and hyperhomocysteinemia, the association with depressive disorders was substantially reduced after adjustment for functional disability and cardiovascular disease, but for vitamin B12 this appeared independent.…”
Section: Vitamins B6 and B12mentioning
confidence: 90%
“…On the other hand low level of neurotransmitter is to be linked with poor nutritional support [10,11,13,22,[26][27][28]. A countless amino acid acts as a precursor for the synthesis of neurochemicals in the brain, such as tryptophan is an essential amino acid and acts as a precursor to the serotonin (sadness, anxiety, aggression, enthusiasm) and hormone melatonin (regulates sleep-wake cycle) in the presence of folic acid and vitamin B12, act as a cofactor for mention cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes tyrosine acts as a precursor to phenylalanine and are converted into dopamine and norepinephrine [2,12,[29][30][31]. Some other studies have suggested the amino acids tryptophan, tyrosine, phenylalanine, and methionine are often helpful in treating many mood disorders including depression through increasing the concentration of monoamines in the brain [11,14,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the American Women's Health and Ageing Study, elderly women with vitamin B 12 deficiency (serum vitamin B 12 ,200 pg/ml) were more than twice as likely to be depressed as non-deficient subjects (4) . In a study from Rotterdam, vitamin B 12 deficiency (serum vitamin B 12 ,350 pg/ml) was significantly related to depression.…”
Section: Comparisons Of Findings With Other Studiesmentioning
confidence: 99%